Lateral Ventricular Epidermoid with Severe Coarse Tremor and Weakness in Opposite Limbs: A Rare Case Report - Chowdhury, Forhad Hossain; Haque, Mohammod Raziul; Kawsar, Khandkar Ali; Haque, Momtazul (Journal of Medicine, 2016)
Intracranial epidermoid tumor is rare and intraventricular epidermoid is further rare. Occurrence of epidermoids is common in posterior carnial fossa. Fourth ventricle is relatively common site for intraventricular epidermoid. Epidermoid tumor in lateral ventricle is very rare. Such a tumor presenting with severe progressive coarse tremor and weakness in opposite side of the body probably had never been reported. The epidermoid was removed by endoscope assisted microsurgical technique. Post operatively patient recovered from tremor limbs weakness. Here we report a very rare case of lateral intraventricular epidermoid with tremor and weakness in opposite limbs as well as surgical techniques with short review of related literatures. J MEDICINE January 2016; 17 (1) : 46-50